Visual Education Based on Eco-Info Board to Increase Environmental Awareness of Tenganan Village Community - Fitri, Titi; Arfah, Muh; Abdul Aziz, Muhammad; Naqiyah, Neni (Universitas Ibn Khaldun Bogor, 2025)
With environmental challenges on the rise, public awareness to conserve nature is of paramount importance. The Eco-Info Board was designed as an engaging informative media, conveying environmental issues, including the negative impact of littering and the importance of environmentally friendly practices. This study aims to determine the effectiveness of the Eco-Info Board in increasing the environmental awareness of the community of Desa Adat Tenganan Pegringsinga n, Kec. Manggis, Kab. Karang Asem, Prov. Bali, in 2024. The method used is quantitative with a pre-experimental design, observing one group after being given treatment. Sampling was conducted using purposive sampling technique, involving 51 respondents from the Tenganan Traditional Village community. The research instrument consisted of observation and questionnaire, with 16 statements tested. The results of this analysis show that the value of Asymp.Sig. (2-tailed) value of 0.000, which means rejecting H0 and accepting Ha, so it can be concluded that visual education based on Eco-Info Board has a positive influence on environmental awareness. The program successfully raises people's awareness to preserve and protect the environment as an expression of respect for God and nature. Hopefully, this research can provide a deeper understanding to the community about the dangers of littering and encourage their active participation in keeping the environment clean.